Synergies between social protection and agriculture - Dadione, Silvio; Rossi, Natalia Winder; Soares, Fabio Veras (International Food Policy Research Institute, 2018)
This chapter analyzes how the interplay of agriculture and social protection programs and policies and their coordinated implementation can create positive synergies that accelerate progress in reducing rural poverty, eliminating hunger, and building resilience and improved well-being, especially for small family farmers. After providing a conceptual framework describing the links between the two domains, we review evidence from the impact evaluation literature and discuss possible policy and programming options to promote coherence and sustainable practices for agriculture and social protection efforts.